Paroxysmal dystonia and neuromyelitis optica - Felipe R. Schmidt; Flavio Henrique R. Costa; Fernanda M.L.C. Silva; Henryk Maultasch; Ana Lucia Rosso; Denise H. Nicaretta; James P. de Mattos; Sergio A.P. Novis; Soniza V Alves-Leon (Arquivos de Neuro-Psiquiatria)
Paroxysmal dyskinesias (PD) are thought to be rare movement disorders. The overwhelming majority of reported cases are primary. Secondary PD has seen reported to occur in some conditions, mainly in multiple sclerosis and head trauma. The anatomic origin of the lesion is also rarely seen at the spinal cord. Our objective was to describe four patients with paroxysmal dystonia secondary to spinal lesions during the recovering phase of a neuromyelitis optica (NMO) bout. In the reviewed literature, we do not find any report of PD related to NMO.